Serum anti-hsp27 antibodies concentration in diabetes mellitus; population based case-control study - Tavana, Mahshid; varasteh, Naiemeh; rohban, mohadese; Ghazizadeh, Hamideh; Sadeghzade, Mahsa; Tavalaie, Shima; Abolbashari, Samaneh; Ramshini, Hossein; meshkat, Zahra; ferns, Gordon; et al. (Archives of Medical Laboratory Sciences, 2020)
Background: Diabetes mellitus is an important risk factor for cardiovascular disease. Different biomarkers have been investigated for the diagnosis of diabetes pathogenesis or its complications. There are also reports regarding an increased level of anti-HSP27 antibodies in atherogenesis. We aimed to evaluate serum anti-heat shock protein 27 antibodies level in subjects with diabetes mellitus and undiagnosed individuals. Materials and Methods: This cross-sectional study was conducted on 6447 MASHAD study subjects, including four groups with diabetes mellitus (n=610), undiagnosed diabetes (n=162), impaired fasting glucose (IFG) (n=619) and normal (n=5056) subjects. Demographic and anthropometric data were obtained from all participants. Fasting serum glucose (FSG) and other parameters were measured. In-house enzyme-linked immune sorbent assay method was used for measuring Anti-HSP27 antibodies levels. Results: There were significant differences in weight (p=0.034), body mass index, waist, and hip circumference, systolic and diastolic blood pressure, fasting serum glucose, lipid profile and high sensitive- C reactive protein (p<0.001) between four groups of diabetes mellitus, undiagnosed diabetes, impaired fasting glucose, and normal subjects. The serum anti-HSP27 antibody titer did not show a significant difference between studied groups. Conclusion: Serum antibody titers to HSP27 were not significantly different between four groups categorized based on their FSG levels in a large population.